Prevalence of obesity and need for screening using tools like Indian Diabetes Risk Scale in Diabetes prevention among medical students - Prabhakar, Vikrant; Virk, Amrit; Singh, Parmal (Indian Journal of Community Health, 2020)
Introduction: The prevalence of lifestyle diseases in increasing throughout the world. They are increasingly taking over communicable diseases as the major cause of morbidity and mortality. Medical students usually have sedentary lifestyle coupled with high level of stress, owing to academic requirements. Hence, they are at a much higher risk of developing lifestyle diseases. Materials and Methods: Study subjects were administered a validated questionnaire to collect information related with the components of IDRS. Based on the score, they were divided into high risk, moderate risk and low risk. Data was analysed using the SPSS version 21. Result: Half of all the students were in the moderate risk group. The rest was distributed among low risk (17.33 %) and high risk (27.33%). Among those with low risk of developing T2DM, 73% were males, whereas females constituted 70.7% of those with high risk of developing T2DM. The association of developing T2DM was also highly significant with obesity. Statistically significant association of high T2DM risk were found with gender being female, family history of T2DM and BMI?23 Kg/m2 Conclusion: IDRS has been shown to be an effective tool for screening populations. Hence, regular programs with IDRS along with blood sugar and lipid profile of moderate and high risk group along with stress management can be effective in supporting medical students to cope with demanding study and work conditions among medical students and doctors.